2015
DOI: 10.1002/cbic.201402550
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Enzymes for ATP Regeneration in Biocatalytic Processes

Abstract: Adenosine-5'-triphosphate-dependent enzyme catalysed reactions are widespread in nature. Consequently, the enzymes involved have an intrinsic potential for use in syntheses of high value products. Although regeneration systems for ATP starting from adenosine-5'-diphosphate are available, certain limitations exist for both in vitro and in vivo applications requiring ATP regeneration from adenosine-5'-monophosphate, or adenosine. Following a short overview of the chemical and thermodynamic background, this Minir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
130
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 109 publications
0
130
1
Order By: Relevance
“…Currently, the most economical way of utilizing CAR enzymes on a preparative scale is their use via whole cell biocatalysts that allows cost effective regeneration of the required co‐factors (ATP, NADPH) 8,38, 39, 40. At the same time, the enzymatic background of bacterial cells rapidly reduces aldehydes ( b ) to the corresponding alcohols ( c ) which minimizes the oxidative and electrophilic stress responses induced by the reactive carbonyl group in aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the most economical way of utilizing CAR enzymes on a preparative scale is their use via whole cell biocatalysts that allows cost effective regeneration of the required co‐factors (ATP, NADPH) 8,38, 39, 40. At the same time, the enzymatic background of bacterial cells rapidly reduces aldehydes ( b ) to the corresponding alcohols ( c ) which minimizes the oxidative and electrophilic stress responses induced by the reactive carbonyl group in aldehydes.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In conclusion, we have shown that in the absence of NADPH, the adenylation activity of CARs can be exploited for amide bond formation. [31] Tw oC AR variants were generated by the rational redesign of the CARs,which possess no reduction activity but retain amido synthetase activity.T he success with these variants suggests that the adenylation activity alone is sufficient for activation of carboxylic acids for subsequent amidation, and also lays the foundations for future work using this method in more complex enzyme systems,s uch as in enzyme cascades or whole-cell biotransformations. [9][10] While our method is limited by the use of the expensive cofactor ATP, this may be Figure 2.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Results and discussion 3.1. Pyruvate kinase and luciferase coupled reactions ATP regeneration systems using inexpensive materials are in demand for the industrial processes using ATP-dependent enzyme, because ATP is an expensive compound [15]. Pyruvate kinase regenerates ATP from ADP, which is a typical product of ATP-dependent enzyme reactions, via the transfer of a phosphate group from phosphoenolpyruvic acid to ADP [16].…”
Section: Multistep Phototriggering Of Coupled Reactions Of Pyruvate Kmentioning
confidence: 99%